Mycotoxins - Impact and Management Strategies 2019
DOI: 10.5772/intechopen.76371
|View full text |Cite
|
Sign up to set email alerts
|

Control of Aflatoxicosis in Poultry Using Probiotics and Polymers

Abstract: An important approach to prevent aflatoxicosis in poultry is the addition of non-nutritional adsorbents in the diet to bind aflatoxin B1 (AFB1) in the gastrointestinal tract. These adsorbents are large molecular weight compounds that are able to bind the mycotoxin, forming a stable complex adsorbent-mycotoxin, which can pass through the gastrointestinal tract. In this chapter, we evaluate the use of polymers and probiotics to reduce AFB1 toxic effects in poultry. Our results on the efficacy of polymers and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 128 publications
(173 reference statements)
0
8
0
Order By: Relevance
“…The metabolites produced work via binding and absorption of mycotoxins onto the bacterial cell walls and utilizing them as primary sources of carbon, nitrogen, and phosphorus in the production of enzymes responsible for the degradation ( Table 3 ) [ 136 ]. Aflatoxins are also removed by LAB through the biodegradation/bioadsorption mechanisms via direct binding based on probiotic affinity toward aflatoxins [ 137 139 ]. Biodegradation of modified AFB 1 structure can result in undesirable metabolites (such as aflatoxin), which are probably harmful to the host [ 137 139 ].…”
Section: Degradation Of Mycotoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolites produced work via binding and absorption of mycotoxins onto the bacterial cell walls and utilizing them as primary sources of carbon, nitrogen, and phosphorus in the production of enzymes responsible for the degradation ( Table 3 ) [ 136 ]. Aflatoxins are also removed by LAB through the biodegradation/bioadsorption mechanisms via direct binding based on probiotic affinity toward aflatoxins [ 137 139 ]. Biodegradation of modified AFB 1 structure can result in undesirable metabolites (such as aflatoxin), which are probably harmful to the host [ 137 139 ].…”
Section: Degradation Of Mycotoxinsmentioning
confidence: 99%
“…Aflatoxins are also removed by LAB through the biodegradation/bioadsorption mechanisms via direct binding based on probiotic affinity toward aflatoxins [ 137 139 ]. Biodegradation of modified AFB 1 structure can result in undesirable metabolites (such as aflatoxin), which are probably harmful to the host [ 137 139 ]. The activities of aflatoxin toxicity are affected by two sites of furofuran and lactone rings.…”
Section: Degradation Of Mycotoxinsmentioning
confidence: 99%
“…Studies have shown that there is the possibility that probiotics can detoxify aflatoxins in two ways. First, aflatoxin can be adsorbed by the wall carbohydrates of probiotics and reduced their bioavailability, and second, the released metabolites of probiotics may degrade aflatoxins (Solis‐Cruz et al ., 2018). Aflatoxins can bind to peptidoglycans and other cell wall polysaccharides.…”
Section: Probiotics' Mechanism Of Action On Aflatoxinsmentioning
confidence: 99%
“…Biodegradation is irreversible and of longer duration compared to bioadsorption, but it can modify toxin structure and also result in unwanted metabolites (e.g., aflatoxicol from aflatoxin B1), which could be detrimental for the host. Bioadsorption assumes quick direct binding of toxin which might be simply released and depends on the bacterial affinity toward toxin [ 57 ]. Bacillus and Brevibacterium species have been studied for degradation of different mycotoxins: aflatoxin, zearalenone, deoxynivalenol, ochratoxin and patulin.…”
Section: Post-harvest Biological Controlmentioning
confidence: 99%